1994
DOI: 10.1182/blood.v84.9.3148.3148
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutations are associated with resistance to chemotherapy and short survival in hematologic malignancies

Abstract: We analyzed the prognostic value of p53 mutations for response to chemotherapy and survival in acute myeloid leukemia (AML), myelodysplastic syndrome (MDS), and chronic lymphocytic leukemia (CLL). Mutations were detected by single-stranded conformation polymorphism (SSCP) analysis of exons 4 to 10 of the P53 gene, and confirmed by direct sequencing. A p53 mutation was found in 16 of 107 (15%) AML, 20 of 182 (11%) MDS, and 9 of 81 (11%) CLL tested. In AML, three of nine (33%) mutated cases and 66 of 81 (81%) no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
155
2
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(175 citation statements)
references
References 26 publications
13
155
2
4
Order By: Relevance
“…Our data demonstrated that dic(17;18)(p11.2;p11.2) is a novel recurrent cytogenetic abnormality in CLL associated with early age at diagnosis, accelerated disease progression, and a trend toward more refractory disease. These features are similar to previously published reports of patients with loss of p53 or del(17p13.1) alone, which found these patients to require early therapy, to have poor response to standard purine analog therapy, and have shortened survival (Fenaux et al, 1992;Wattel et al, 1994;Dohner et al, 1995;Cordone et al, 1998;Oscier et al, 2002). Within this subset of del(17p.13.)…”
Section: Discussionsupporting
confidence: 88%
“…Our data demonstrated that dic(17;18)(p11.2;p11.2) is a novel recurrent cytogenetic abnormality in CLL associated with early age at diagnosis, accelerated disease progression, and a trend toward more refractory disease. These features are similar to previously published reports of patients with loss of p53 or del(17p13.1) alone, which found these patients to require early therapy, to have poor response to standard purine analog therapy, and have shortened survival (Fenaux et al, 1992;Wattel et al, 1994;Dohner et al, 1995;Cordone et al, 1998;Oscier et al, 2002). Within this subset of del(17p.13.)…”
Section: Discussionsupporting
confidence: 88%
“…It may be particularly useful in the treatment of patients who are resistant to standard chemotherapy as it appears not only to mediate its effect through a p53-independent pathway but also seems to circumvent the Bcl-2 family mediated inhibition of apoptosis commonly seen in B-CLL. In the context of previous findings that have demonstrated a link between p53 mutation, failed apoptosis, non-responsiveness to therapy and poor prognosis in B-CLL (El Rouby et al, 1993;Wattel et al, 1994;Dohner et al, 1995), flavopiridol represents a relevant and timely addition to the chemotherapeutic arsenal for the treatment of this condition.…”
Section: Discussionmentioning
confidence: 90%
“…The modest contribution of p53 to the nucleoside-induced killing of CLL cells suggests that the poor clinical response to nucleoside therapy observed in CLL patients with p53 abnormalities (Wattel et al, 1994;Dohner et al, 1995) is unlikely to be due to nucleoside resistance at the time of diagnosis. A more likely scenario is that the genomic instability associated with p53 dysfunction (Ko & Prives, 1996) facilitates the evolution during the course of the disease of CLL cell clones (including large-cell transformations (Lens et al, 1997)) that have become resistant to nucleosides for reasons not directly connected with p53.…”
Section: Resultsmentioning
confidence: 99%
“…It is now clear that CLL patients with p53 gene abnormalities have a short survival and respond poorly to therapy with purine analogues (Wattel et al, 1994;Dohner et al, 1995). However, the cellular basis for this important clinical observation is far from clear.…”
Section: Discussionmentioning
confidence: 99%